High Initial Concrete Compressive Strength with Variations of Superplasticizer and Silica Fume Additions - Rizal, Nanang S.; Arifi, Eva; Mufarida, Nely A. (Civil Engineering Journal, 2025)
Concrete is one of the construction materials resulting from a combination of cement, fine aggregate, coarse aggregate, and water, which are mixed into a solid mass and then can be added with minerals (additives) or chemical additives (admixtures). The purpose of this study is to produce high-quality concrete that is optimum at the early age of the concrete so that the concreting time can be shortened, including by adding superplasticizer as a filler and silica fume as an accelerator. This research method involves making a cylindrical test object with a diameter of 15 cm and a height of 30 cm. Then, the concrete mixture is added with silica fume brand Sika Fume and superplasticizer brand Sika Concrete produced by PT. Sika with 19 variations of the mixture composition; the compressive strength test of the concrete is carried out at 3 days, 7 days, and 28 days. The findings are that 75% of concrete samples using additional materials in the form of silica fume and superplasticizer are quite significant in increasing the initial compressive strength of the concrete by up to 30% both at the age of 3 days, as well as at the age of 7 days and 28 days. The use of additional materials in the form of silica fume and superplasticizer in concrete mixtures with the right levels can generally improve the quality of concrete in its initial compressive strength at the age of 3 days or its workability or fluidity. However, silica fume and superplasticizer materials, when entered into concrete, have mutually influenced performance. The innovation is that high-quality concrete that is optimum at an early age of concrete can be done easily and cheaply using materials that are easily found in the field by combining superplasticizer as a filler and silica fume as an accelerator. Doi: 10.28991/CEJ-2025-011-01-07 Full Text: PDF